Ionization of large helium nanodroplets. Issue 12 (January 2020) - Lundberg, L; Laimer, F; Martini, P; Kranabetter, L; Tiefenthaler, L; Albertini, S; Zappa, F; Gatchell, M; Scheier, P
Synopsis: We have produced and mass-selected large, highly charged helium droplets containing up to 10 10 He atoms and several tens of charges. They are stable with both multiple positive and negative charge carriers and are stabilized by losing small fragments of excess charge instead of disintegrating (highly asymmetric fission).